Contribuciones a la pteridología costarricense. IV. Los géneros Cheiloplecton, Schaffneria y Paltonium en Costa Rica - Gómez P., Luis D. (1973)
Two genera of ferns, Cheiloplecton and Schaftneria, known only from Mexico and Guatemala, are reported from Costa Rica. A third genus, Paltonium, described from the West Indies and an exclusive epiphyte of the Caribbean Basin, ranging from Florida to the Lesser Antilles and from Yucatan to Venezuela, is represented in Costa Rica by a single population on the Pacific slopes of the Cordillera Volcánica de Guanacaste.